PRINSIP LIBERALISME DALAM METODOLOGI TAFSIR FEMINIS: PEMBACAAN PADA KARYA KARYA HUSEIN MUHAMMAD - Zulaiha, Eni; Busro, Busro (UIN Antasari Banjarmasin, 2020)
This study examines the use of liberal principles in Husein Muhammad's works on Quranic interpretation which are found when uses new concepts of the Sciences of the Qur?an. This new concept is used as an ontological view when he interprets Qur'anic verses regarding human rights and gender relations. The liberal principles that Husein Muhammad uses have clear parameters and do not neglect the basic rules of interpretation itself. Through a qualitative approach with descriptive method, research on literature and interviews, this study confirms that the liberal principles used by Husein Muhammad, in addition to using gender justice analysis, are also produced among others through a re-understanding of the rules of interpretation such as asbuz nuzul, n?sikh mans?kh, ta`w?l, muhkam-mutasy?bih, makkiyah mad?niyyah. The redefinition of the rules of interpretation is then used as the basis when he makes the interpretation of the Qur'an so that the results of the interpretation are different when compared to interpretations that have been developed among Muslims. As a result, his interpretation is not only laden with religious messages, but also becomes part of the expression of feminist kiyai identity in the development of interpretations in Indonesia.